Identifikasi Mikrobiologi Ikan Asap dan Persepsi Konsumen terhadap Mutunya pada Berbagai Tingkat Distribusi di Kota Semarang - Safira, Mas Ayu; Rohadi, Rohadi; Cahyanti, Antonia Nani (Faculty of Agricultural Technology, Universitas Semarang, 2024)
Smoked fish is one of the traditional processed products that almost all types of fish can be used as raw materials. Smoking processing is done by utilizing a combination of treatments and the provision of natural chemical compounds from the combustion of natural fuels. This study aims to determine the microbiological quality of smoked fish and consumer perception of its quality at various distribution levels in Semarang City. The experimental design used in this study was one factor Randomized Group Design: different distribution levels. Parameter observed were Total Plate Count (TPC), Salmonella sp. identification, and sensory properties of smoked fish. The results showed that of the three distribution levels, smoked fish from the producer had the best microbiological quality and consumer perception value, with an average TPC values of 1,66 × 105 colonies/gram, no Salmonella sp. contamination was detected, and had an average sensory value of 9,75. Thisvalues is in accordance with the quality standards of smoked fish with hot smoking listed in SNI 2725:2013. The data showed that different distribution levels influenced consumer perception and microbiological quality of smoked fish in Semarang City.